A note on independent domination of zero-divisor graphs - Mojdeh, Doost Ali,; Habibi, Mohammad, (Utilitas Mathematica, 2017)
In this note, we determine the independent domination number of a zero-divisor graph of the ring Zpα × Zqβ, where p and q are prime numbers. We show that the independence domination number of zero-divisor graphs these rings can be characterized by Eulerian φ-numbers of the order of rings. © 2015 Utilitas Mathematics.